Environmental impact of point pollution sources - De Lange, Stephanus Steyn (University of the Free State, 1999)
Due to the importance of groundwater as an alternative for supplementing existing sources of this precious fluid, any study that may help in understanding the complexity of the groundwater environment is an asset. Therefore this dissertation was written with the sincerest hope that the people and organisations involved with groundwater will gain a better understanding of it. The need to protect our groundwater sources has become very important and therefore a different, more practical approach to delineate borehole protection zones was considered based on the existing standards set by Germany and other European nations. As part of the study, emphasis was placed on the effect of the unsaturated (vadose) zone on the migration of pollutants before it reaches the groundwater environment. Field tests on the saturated as well as unsaturated zones were conducted with a conservative tracer (Fluorecein) as well as microbial tracers (bacteriophages), to assist in the delineation process. Thereafter it was decided to propose that three protection zones should be assigned depending on i) the size of the population and ii) the vulnerability and importance of the aquifer. The effect of a pollutant on human health and the possibility of fatalities were the criteria for deciding which protection zone is applicable under given circumstances. Protection zone I involves fencing off the immediate area around the borehole (a radius of 5 m is proposed) as well as the necessity of a well-constructed sanitary seal. Where a borehole supplies water to less than 20 people, a sanitary seal will be sufficient. To determine the extent of protection zone II, the idea was to protect the drinking water from microbial (bacteria and viruses) and nitrate pollution. Emphasis was placed on these two parameters because of their association with pitlatrines and septic tanks. Methods to estimate the fracture extent are proposed and, depending on the estimation of the nitrate and bacterial travel times and loads, a guideline to use i) half the fracture extent, ii) the whole extent of the fracture or iii) double the fracture extent, is proposed. Only if there is the possibility of a hazardous substance that may pollute the groundwater, it is proposed that protection zone III be assigned. The use of the word "hazardous" could make the decision more complex and therefore the issue of risk assessment and management is also addressed very generally in this dissertation. The proposed extent for protection zone III is the whole catchment area of the borehole. A programme called Borehole Protection Zone (BPZONE) was developed by making use of Microsoft Excel to assist the person(s) responsible in the decision making processes of delineating borehole protection zones. Information gathered during the field tests conducted at the Campus Test Site of the University of the Free State as well as the Meadhurst Test Site outside Bloemfontein, yielded very positive results, in terms of delineating protection zones.

A.g.v. die belangrikheid van grondwater as 'n alternatief ter aanvulling van die kosbare vloeistof, is enige studie wat sal meebring dat die ingewikkelde meganismes van die grondwateromgewing beter verstaan word, 'n voordeel. Dus is die verhandeling saamgestel met die hoop dat persone en organisasies wat met grondwater te doen het, baat daarby sal vind. Die beskerming van ons grondwaterbronne het baie belangrik geword en dus is gepoog om met 'n verskillende, meer praktiese benadering, boorgatbeskermingsones toe te ken. Huidige standaarde wat deur Duitsland en ander Europese lande gebruik word, is as basis gebruik. As deel van die studie is klem gelê op die effek van die onversadigde sone op die beweging van besoedeling voordat dit die grondwater bereik. Veldtoetse in die versadigde, sowel as onversadigde sones, is gedoen met 'n konserwatiewe spoorder (Fluorecein), asook mikrobiese spoorders (bakteriofages), om met die toekenning van beskermingsones te help. Daar is besluit om sones toe te ken wat beïnvoed word deur i) die populasie en ii) die kwesbaarheid en belangrikheid van die akwifeer. Die effek van besoedeling op menslike gesondheid en die moontlikheid dat sterfgevalle kan voorkom is gebruik as kriteria om te besluit watter beskerming sone is toepaslik onder sekere omstandighede. Vir beskermingsone I word voorgestel dat die onmiddelike omgewing rondom die boorgat toegekamp moet word ('n afstand van 5 m word voorgestel) asook die oprig van 'n goeie sanitêre seël. Waar 'n boorgat water verskaf aan minder as 20 mense, behoort slegs 'n sanitêre seël genoegsaam te wees. Met die toekenning van beskermingsone II was die idee om die drinkwater teen mikrobiese (bakterië en virusse) asook nitraat besoedeling te beskerm. Die klem het op die twee parameters geval a.g.v. hulle assosiasie met pitlatrines en septiese tenksisteme. Metodes om die grootte van 'n fraktuur te skat word voorgestel en afhangende van die mate van nitraat en bakteriologiese bewegingstye (E. travel times) en ladings word drie riglyne voorgestel. i) helfte van die fraktuurgrootte, ii) die hele fraktuurgrootte en iii) dubbeld die fraktuurgrootte. Slegs as daar 'n moontlikheid is dat 'n gevaarlike (E. hazardous) stof die grondwater kan besoedel, word voorgestel dat beskermingsone III toegeken word. Die gebruik van die woord "gevaarlik (E. hazardous)" maak die besluit meer kompleks en daarom is die kwessie van risikowaardering en bestuur baie algemeen in die verhandeling aangespreek. Die voorgestelde grootte vir beskermingsone III sluit die hele opvangsgebied van die boorgat in. 'n Program genoem Borehole Protection Zone (BPZONE) is ontwikkel deur gebruik te maak van Microsoft Excel om die persoon(e) wat verantwoordelik is vir die besluitnemings proses t.o.v. toekenning van boorgat beskerming sones met dié besluit te help. Inligting wat gedurende veld toetse versamel is by die Kampus Toetsterrein van die Universiteit van die Vrystaat asook by die Meadhurst Toetsterrein buitekant Bloemfontein, het baie positiewe resultate opgelewer.
Keywords: Groundwater -- Pollution -- South Africa; Environmental protection -- South Africa; Groundwater -- Quality -- South Africa; Dissertation (M.Sc. (Geohydrology))--University of Free State, 1999